Association between platelet-to-red cell distribution width ratio and all-cause mortality in critically ill patients with non-traumatic cerebral hemorrhage: a retrospective cohort study - Lu, Rongrong; Wu, Changcai (Frontiers in Neurology, 2024)
BackgroundThe purpose of this study was to investigate the relationship between platelet-to-red cell distribution width ratio (PRR) and all-cause mortality in critically ill patients with non-traumatic cerebral hemorrhage (NCH).MethodsThe Medical Information Mart for Intensive Care (MIMIC-IV) database was used to identify patients with NCH who needed to be admitted to intensive care unit (ICU). The outcomes of the study included both ICU and in-hospital mortality. Restricted cubic splines and Cox proportional hazards regression analysis were used to clarify the relationship between PRR and clinical outcomes in critically ill patients with NCH.ResultsA total of 3,094 patients (54.0% male) were included in the study, with in-hospital mortality and ICU mortality rates of 16.5 and 11.8%, respectively. A substantial correlation was found by multivariate Cox proportional hazards analysis between increased PRR and a lower risk of in-hospital and ICU mortality. Following adjustment for confounding factors, patients with elevated PRR exhibited a significantly decreased risk of in-hospital death (HR, 0.98; 95% CI, 0.96–0.99; p = 0.006) and ICU death (HR, 0.98; 95% CI, 0.96–0.99; p = 0.027). As PRR increased, restrictive cubic splines showed a progressive decrease in the probability of all-cause mortality. Stratified analyses indicated a consistent association between PRR and both in-hospital and ICU mortality.ConclusionAmong critically ill patients with NCH, lower PRR was substantially correlated with the increased probability of all-cause mortality in both the ICU and hospital. According to this research, PRR might be a valuable indicator for identifying NCH patients at risk of all-cause mortality.